2018
DOI: 10.14716/ijtech.v9i1.1165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metal Loading on the Performance of Tri-metallic Supported Catalyst for Carbon Nanotubes Synthesis from Liquefied Petroleum Gas

Abstract: Carbon nanotubes (CNT) were synthesized from liquefied petroleum gas by a chemical vapor deposition method using a Fe-Co-Mo/MgO supported catalyst. Metal loading was varied from 2.5 to 20 wt%. The catalyst with metal loading of 10 wt% produced the highest CNT yield, at 4.55 g CNT/g catalyst. This high CNT yield was attributed to the high pore volume of the catalyst. The diameter of the CNT was quite variable: the outer diameter ranged from about 4 to 12 nm, while the inner diameter ranged from about 2 to 5 nm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has demonstrated that the pore volume of the catalyst may have an important effect on the CNT yield. The high capacity of pore volume promotes the reduction of the barriers to diffusion and transport, which enable biogas molecules to distribute deep into the inner surface of the catalyst and result in a higher CNTs yield 57 . Besides, it has been reported that the Mo 2 C phase enhances the diffusivity of carbon atoms into neighboring Ni nanoparticles, avoiding the encapsulation of carbon deposition and leading to CNT growth 42 , 58 .…”
Section: Resultsmentioning
confidence: 99%
“…It has demonstrated that the pore volume of the catalyst may have an important effect on the CNT yield. The high capacity of pore volume promotes the reduction of the barriers to diffusion and transport, which enable biogas molecules to distribute deep into the inner surface of the catalyst and result in a higher CNTs yield 57 . Besides, it has been reported that the Mo 2 C phase enhances the diffusivity of carbon atoms into neighboring Ni nanoparticles, avoiding the encapsulation of carbon deposition and leading to CNT growth 42 , 58 .…”
Section: Resultsmentioning
confidence: 99%
“…CNTs are allotropes of the carbon family with hollow cylinder structures. Based on the chirality angle divergence of the graphene sheet, their electronic properties may vary between metallic and semiconducting CNTs exist as single-walled, dual-walled or multiwalled (Setyopratomo et al, 2018;Thanthirige et al, 2016). Consisting only of surface (i.e., no bulk C-atoms), they are extremely sensitive and responsive to surface modification and optical excitation.…”
Section: Introductionmentioning
confidence: 99%